PENGARUH DISKON, BONUS KEMASAN, TAMPILAN TOKO, DAN PENJUALAN PERORANGAN TERHADAP PEMBELIAN IMPULSIF - Karin Ryanda Saputri, 15.05.51.0197; Maskur, Ali (Students' Journal of Economic and Management, 2019)
This study aims to determine the effect of price discount, bonus pack, in-store display and personal selling on impulse buying at supermarket customers ADA Siliwangi. This research was conducted at the ADA Siliwangi Supermarket located on Jl. MgrSugiyopranoto No.58-60, Bulustalan, Semarang City. In this study the population is all consumers who have made purchases to the ADA Siliwangi Supermarket Semarang. The sample taken was 110 respondents. The sampling technique uses non probability sampling. Data collection techniques using questionnaires that have been tested for validity and reliability, and the data analysis technique used is multiple regression. The results showed that (1) there was a positive and significant effect of price discount on impulse buying on ADA Siliwangi supermarket customers, (2) there was a positive but not significant effect between bonus pack on impulse buying on ADA Siliwangi supermarket customers, (3) there were positive influences but not significant between the in-store display of the impulse buying at ADA Siliwangi supermarket customers, (4) there is a positive and significant effect of personal selling of impulse buying at ADA Siliwangi supermarket customers.